Ensuring the right to higher education: A general overview - Sharapov Shukhrat (Annals of Justice and Humanity, 2025)
Purpose: This study aims to examine the right to higher education as a fundamental human right and a key state obligation. It seeks to analyze international legal frameworks, national constitutions, and comparative experiences from Germany, Indonesia, Russia, and Uzbekistan to identify how legal reforms, policy mechanisms, and financial measures ensure equitable access to higher education. Methods: Using a qualitative and comparative approach, the study applies doctrinal legal analysis of primary sources such as the Universal Declaration of Human Rights, ICESCR, and UNESCO Conventions, alongside national education laws. Secondary data from academic research, government reports, and statistical evidence were analyzed through content analysis to evaluate legal and institutional guarantees. Results: Findings reveal that while international norms recognize higher education as a universal right, its realization varies among countries. Germany ensures free university access; Russia offers merit-based state-funded higher education; Indonesia guarantees education through constitutional budget allocation; and Uzbekistan demonstrates rapid progress through legislative reforms, expansion of institutions, and increased enrollment rates. Conclusion: Ensuring the right to higher education requires a balance between accessibility, quality, and equity through sustained state commitment and international cooperation. Limitation: The research focuses on selected case studies and does not include empirical fieldwork or student-level data, limiting its scope of generalization. Contribution: This paper contributes to comparative educational law by linking global human rights frameworks with national implementation models, providing policy insights for developing inclusive and equitable higher education systems.